Pengaruh Arus Kas dan Ukuran Perusahan terhadap Financial Distress: Studi Kasus Perusahaan Transportasi dan Logistik (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This research aims to determine the extent of the influence of Cash Flow and Company Size on Financial Distress in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This type of research is quantitative research using secondary data sources taken from the company's financial statements published through the official website of the Indonesia Stock Exchange (IDX). The sampling technique used is the purposive sampling method with a sample size of 9 companies over a period of 5 years. The data analysis technique uses IBM SPSS 24 software by conducting several tests, namely descriptive statistical tests, classical assumption tests, multiple linear regression analysis, hypothesis tests and determination coefficient tests. The results of this study indicate that partially cash flow has a positive effect on financial distress, this is evidenced by the results of the t-test of 3.599 which is greater than the t-table of 2.01954 with a sig value of 0.01 <0.05. Company size partially does not have a significant effect on financial distress, this is evidenced by the results of the t-test of 0.921 which is smaller than the t-table of 2.01954 with a sig value of 0.362> 0.05. Simultaneously, cash flow and company size have a significant effect on financial distress, this is evidenced by the results of the f-test of 6.918 which is greater than the f-table of 3.23 with a sig value of 0.003 <0.05.